Hardness and Microstructural Characterization of Pack Carburizing AISI 1020 Low-Carbon Steel by Temperature and Holding Time Variations - Santoso, Edi; Fatkhurrohman, Fatkhurrohman; Firmansyah, Addie Restu; Putra, Septian Candra (Universitas PGRI Semarang, 2024)
Recently, low-carbon steel is often used as a basic material for automotive spare parts on the market. This study aims to improve the quality of carbon steel which is not inferior to that made by manufacturers where the price is relatively affordable by carrying out pack carburizing. This study used the pack carburizing method, AISI 1020 low-carbon steel as a starting material and used fine coconut shell charcoal powder as a carbon source mixed with Na2CO3 as an energizer. Pack carburizing uses temperature variations of 850oC, 875oC and 900oC, aims to find out how the results of hardness and microstructure values for variations of temperature and holding time. And also use SAE 20w-40 oil as a quenching medium. The highest hardness results were obtained on specimens with a heating temperature of 900oC with a holding time of 60 minutes, with an average hardness value of 54.21 HRC. Accompanied by the phase formed, namely 61% pearlite 39% ferrite.